Managing Metabolic Syndrome and CHD Risk Factors: Evidence based re-examination of macro nutrients from the Malaysian Population Prospective Study - Sundram, Kalyana (Indian Journal of Community Health, 2014)
Our understanding of dietary factors and habits associated with coronary heart disease (CHD) risk are undergoing dramatic rethinking in light of fast emerging new scientific data. Multiple risk assessments, especially in understanding Metabolic Syndrome triggers in the population have further confounded understanding and management of traditional risk factors. By far the largest change-impact is being made with regard to fat consumption, especially saturated fats. Emerging evidence, largely through meta-analysis and population studies have regularly challenged the association of saturated fats with increased CHD risk. Indeed there is a growing appreciation that saturates no longer glove-fit risk assessment especially when newer biochemical factors such as lipoprotein particle sizes have emerged to partially explain observed anomalies. The fats we eat may not necessarily be associated with making us fat (obese) and obesity is a major health challenge globally. This has redirected dietary assessments more towards excess carbohydrate consumption and their possible adverse outcomes. Drawing on an ongoing population prospective study in Malaysia, such observations are similarly amplified in an urban Malaysian population. Significant carbohydrate associated negative impacts on CHD risk is seen emerging, especially when evaluated against more advanced biochemical markers. Differences in the ethnic groups of the population, modulated through cultural dietary preferences are similarly apparent. In this model, a surprisingly lower risk contributor is the prevailing fat consumption trends in the country. These observations are explained in this presentation aimed at creating better awareness of food factors impacting disease outcomes in an urban Malaysian environment whose make-up includes a substantive South Indian population as well.